2022
DOI: 10.1021/acsnano.2c05303
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Active Learning for Scanning Probe Microscopy: From Gaussian Processes to Hypothesis Learning

Abstract: Recent progress in machine learning methods and the emerging availability of programmable interfaces for scanning probe microscopes (SPMs) have propelled automated and autonomous microscopies to the forefront of attention of the scientific community. However, enabling automated microscopy requires the development of task-specific machine learning methods, understanding the interplay between physics discovery and machine learning, and fully defined discovery workflows. This, in turn, requires balancing the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…We implemented our system in an experimental set up and demonstrated that the strain mapping task can be performed in nearly 2.4 h instead of the typical 6 h for a specific study on an AM steel part. Our work builds on a larger trend of moving towards autonomous scanning probe imaging systems [18,25] in cases where the time to measure is significantly higher than the sum of the time to re-position the object and computation of the next informative measurement to make. In such systems, there can be an overall saving in experimental measurement time while providing a progressively improved image resolution by employing a powerful algorithm that can infer the underlying structure from a sparse set of measurement points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We implemented our system in an experimental set up and demonstrated that the strain mapping task can be performed in nearly 2.4 h instead of the typical 6 h for a specific study on an AM steel part. Our work builds on a larger trend of moving towards autonomous scanning probe imaging systems [18,25] in cases where the time to measure is significantly higher than the sum of the time to re-position the object and computation of the next informative measurement to make. In such systems, there can be an overall saving in experimental measurement time while providing a progressively improved image resolution by employing a powerful algorithm that can infer the underlying structure from a sparse set of measurement points.…”
Section: Discussionmentioning
confidence: 99%
“…where X prev is the set of all the previous locations on the grid at which a measurement has been made. This type of approach is called BO [25] because we effectively compute the posterior distribution parameters based on some underlying prior model to infer the next point(s) to measure. A simple acquisition function is one that simply uses the variance estimates ('uncertainty') at each position from equation ( 5) and chooses to measure the next point at the position corresponding to the highest variance.…”
Section: Gp Regression and Bomentioning
confidence: 99%
“…DKL poses to be one of the potential solutions to the problems that are discussed so far. DKL is a method that combines the power of deep neural networks with the flexibility of Gaussian Processes (GPs) to model and make predictions on complex target functions in high-dimensional spaces [59][60][61][62][63]. The ability to efficiently explore the high-dimensional input space and learn the relationship between the inputs and target function, makes it a powerful tool for optimization and prediction tasks.…”
Section: Latent Distributions For the Dkl Of Model Datamentioning
confidence: 99%
“…Moreover, much of modern microscopy has advanced with applications of deep learning [16] and other machine learning methods, [17] assisting in everything from data cleaning, [18] to improved functional fits, [19] image segmentation, [20] and recently, to autonomous microscopy operations. [21,22] Therefore, datasets should be able to be used in distributed systems or supercomputer centers. As such, with the recent advancement in automated platforms, standardizing the data model and processing pipelines is an imperative for maximizing the utility of microscopy, and for reducing the significant bottlenecks in the analysis, storage, processing, and retrieval that are currently within traditional experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%